Problems of youth for family life - Norbovaevna , Muratova Shoista (International Journal of Psychosocial Rehabilitation, 2020)
This article examines some of the problems encountered in preparing young people for family life, family relationships in adolescence, important tasks in preparing them for family life, morality, diligence, social behavior, and hygienic and sexual education in the family, school and all educational institutions. Careful consideration of issues, pre-marital factors, motives for marriage, the timing, terms and conditions of acquaintance, their future family life and features as the whole.